(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article highlights the theoretical foundations and practical features of implementing inclusive education in the preschool education system. The content of inclusive education, its pedagogical and organizational aspects, the use of individual educational programs (IEP), the development of multidisciplinary collaboration, as well as the necessity of teacher training and professional development, are scientifically analyzed.